Kurash - Abdilxatovich, Boymirzayev Asadullo; Jahongir, Karimov (European Journal of Life Safety and Stability (2660-9630), 2023)
In this article, the history of the sport of wrestling, this sport is developing in our country There will be talks about finding trends, achievements, competitions. From him The results of the Uzbek athletes in the world arenas will be analyzed.